TERRITORIAL EXPANSION AND REGIONAL INTEGRATION: THE HISTORICAL AND SPATIAL EVOLUTION OF THE RMSM - dos Santos Barbosa, Ronaldo; de Oliveira Araújo, Rafael; dos Santos Lima, Luzivan (Revista Gênero e Interdisciplinaridade, 2026)
Metropolitan regions are central instruments for territorial planning and inter-federative coordination in Brazil, acting as hubs for growth and innovation. This article analyzes the historical and spatial evolution of the South Maranhão Metropolitan Region (RMSM), investigating how its territorial expansion influences regional integration. The methodology adopts a historical-spatial approach based on the analysis of state legislation and socioeconomic data. The results demonstrate that the RMSM underwent significant growth, expanding from eight municipalities at its inception, through Complementary Law No. 089/2005, to twenty-two entities in 2017, via Complementary Law No. 204/2017. It is evident that this expansion was not merely geographical but was accompanied by the creation of governance structures, such as AGEMSUL, and the strengthening of development-inducing institutions, such as UEMASUL. The study concludes that, although the institutional arrangement has advanced, effective regional integration still faces coordination and financing challenges, making the analysis of territorial dynamics essential to convert legal expansion into sustainable and equitable development.